There is no association between premature ovarian insufficiency and levels of fetuin-A/α2-Heremans-Schmid glycoprotein - A Seval Ozgu-Erdinc; Zeynep Asli Oskovi Kaplan; Yaprak Engin-Ustun; Nafiye Yilmaz; Gulcin Yildirim; Aytekin Tokmak; Kudret Erkenekli; Salim Erkaya; Dilek Uygur (Wolters Kluwer Medknow Publications, 2019)
Objective: Fetuin-A is a well-known negative acute-phase protein and has been used liberally to predict vascular disease. The aim of this study was to evaluate the association between serum human fetuin-A/alpha2-Heremans-Schmid glycoprotein levels and idiopathic premature ovarian insufficiency (POI). Methods: A total of 75 women were included in this case-control study between January 2013 and December 2013. Serum fetuin-A concentrations were measured in 36 women with idiopathic POI and 39 healthy women with regular cycles. Blood samples were drawn after a 12-h overnight fast and were kept at −80°C for subsequent assay. The serum levels of fetuin-A were assessed by commercial ELISA kits (BioVendor Laboratory Medicine Inc., Brno, Czech Republic) and serum concentration values were expressed as μg/ml. Results: The mean serum fetuin-A levels of idiopathic POI and control women were 229.02 ± 27.79 and 232.37 ± 65.56, respectively, with P = 0.771 (independent samples t-test). Our results showed no statistically significant difference between serum fetuin-A levels of idiopathic POI women and controls. Conclusion: The mean values of serum fetuin-A in idiopathic POI women were not significantly different from controls, which implies that there is no significant association between serum fetuin-A levels and idiopathic POI.